An electronic quantum eraser - Weisz, E.; Choi, H. K.; Sivan, I.; Heiblum, M.; Gefen, Y.; Mahalu, D.; Umansky, V. (Science (American Association for the Advancement of Science), 2014)
The quantum eraser is a device that illustrates the quantum principle of complementarity and shows how a dephased system can regain its lost quantum behavior by erasing the "which-path" information already obtained about it. Thus far, quantum erasers were constructed predominantly in optical systems. Here, we present a realization of a quantum eraser in a mesoscopic electronic device. The use of interacting electrons, instead of noninteracting photons, allows control over the extracted information and a smooth variation of the degree of quantum erasure. The demonstrated system can serve as a first step toward a variety of more complex setups.